Reassessing the impact of the ASEAN-India free trade agreement - Tham, Siew Yean; Kam, Andrew Jia Yi (Penerbit Universiti Kebangsaan Malaysia, 2014)
The ratifcation of the ASEAN-IndiaF ree TradeA greement( AIFTA)in 2009 signals a potentialfor increasedt radefiows betweenA SEANan d India. Previous studies havefocussedm ainly on the welfare impact of the agreementa nd its impact on overall trade, especially trade in agricultural products. Thefrst objective ofthis study seeks to compare the impact ofthe urrl on the exports ofmanufactured goodsf rom ASEANto India and vice versa. The second is to ascertain the relative importance of the scheduled tariff liberalization in the AIFTA compared with other contributory factors in the export of mandactured goods betweenA SEANa nd India. The study usesa n augmentedg ravity model as this type of model allowsfor the control of other trade related variables and to quantifu any changes in a country's trade due to the agreement.T hem ainfindings in this study indicate that ASEANga ins morefrom the scheduledt ariff liberalization in this agreement compared to India. However, the impact of tariff liberalization on the exports of manufactured goods from ASEANa nd India with each other is relatively smaller compared to other contributory factors, especially trade costs. The AIFTAw ill have to strengthens pecifc tradef acilitation measuresi n the agreementi n order to increase exports of manufactutredg oodsf rom ASEANto India and vice versa.